Stocks and Productivity of Dead Wood in Mangrove Forests: A Systematic Literature Review - Mugi, Lilian Mwihaki; Kiss, Dora; Kairo, James Gitundu; Huxham, Mark Richard (Frontiers in Forests and Global Change, 2022)
The functional and ecological importance of dead wood in terrestrial forests is widely recognized and researched. In contrast, much less is known about dead wood in mangrove forests, despite its known or demonstrated contribution to key ecological processes including nutrient cycling and seedling recruitment. In addition, mangrove dead wood provides an important service for millions of people; harvesting wood for fuel is widespread in mangroves and is often vital for the lives and well-being of people living close to these forests. Limited information on stocks and production, and the drivers of these, means that understanding and managing the supply of this service is difficult. Here we conduct a systematic review of the literature on dead wood stocks and production in mangrove ecosystems. 475 subject articles were found, with large gaps in geography, species, and forest type. After excluding records that were not relevant to our study and those from mass mortality events, 68 studies remained. We also added new data from 9 sites in Kenya, to provide overall estimates of mean (± SD) stocks of dead wood of 16.85 ± 25.35 Mg ha-1 standing and 29.92 ± 36.72 Mg ha-1 downed. Our analysis shows that potentially, higher stocks of dead wood might be found in forests without evidence of human impact. Average mean production with 95% CI was 6.30, 3.10 – 11.40 Mg ha-1yr-1. Estimates of daily wood use were applied to give likely demands on wood from mangrove dependent communities. This review reveals the paucity of research on mangrove dead wood, hence these estimates of average stocks and productivity remain very limited and thus, further work on the dynamics of dead wood in mangroves and the ecological effects of its removal is needed.